Correlation of A2bAR and KLF4/KLF15 with Obesity-Dyslipidemia Induced Inflammation in Uygur Population. (21st April 2016) - Wang, Cuizhe; Ha, Xiaodan; Li, Wei; Xu, Peng; Gu, Yajuan; Wang, Tingting; Wang, Yan; Xie, Jianxin; Zhang, Jun
Abstract : In this paper, the researchers collected visceral adipose tissue from the Uygur population, which were divided into two groups: the normal control group (NC, n = 50, 18.0 kg/m 2 ≤ BMI ≤ 23.9 kg/m 2 ) and the obese group (OB, n = 45, BMI ≥ 28 kg/m 2 ), and then use real-time PCR to detect the mRNA expression level of key genes involved in inflammation signaling pathway. The findings suggest that, in obese status, the lower expression level of A2bAR, KLF4, and KLF15 of visceral adipose tissue may correlate with obese-dyslipidemia induced inflammation in Uygur population.